The canonical semantic network supports residual language function in chronic post‐stroke aphasia. Issue 3 (16th December 2016) - Griffis, Joseph C.; Nenert, Rodolphe; Allendorfer, Jane B.; Vannest, Jennifer; Holland, Scott; Dietz, Aimee; Szaflarski, Jerzy P.
Abstract: Current theories of language recovery after stroke are limited by a reliance on small studies. Here, we aimed to test predictions of current theory and resolve inconsistencies regarding right hemispheric contributions to long‐term recovery. We first defined the canonical semantic network in 43 healthy controls. Then, in a group of 43 patients with chronic post‐stroke aphasia, we tested whether activity in this network predicted performance on measures of semantic comprehension, naming, and fluency while controlling for lesion volume effects. Canonical network activation accounted for 22%–33% of the variance in language test scores. Whole‐brain analyses corroborated these findings, and revealed a core set of regions showing positive relationships to all language measures. We next evaluated the relationship between activation magnitudes in left and right hemispheric portions of the network, and characterized how right hemispheric activation related to the extent of left hemispheric damage. Activation magnitudes in each hemispheric network were strongly correlated, but four right frontal regions showed heightened activity in patients with large lesions. Activity in two of these regions (inferior frontal gyrus pars opercularis and supplementary motor area) was associated with better language abilities in patients with larger lesions, but poorer language abilities in patients with smaller lesions. Our results indicate that bilateral language networks support language processing after stroke, and that right hemispheric activations related to extensive left hemispheric damage occur outside of the canonical semantic network and differentially relate to behavior depending on the extent of left hemispheric damage. Hum Brain Mapp 38:1636–1658, 2017 . © 2016 Wiley Periodicals, Inc.